Inovasi Manajemen Pendidikan Agropreneurship dalam Pengembangan Ekonomi Pesantren: Studi Kasus PPI 97 Cikajang - Siti Aminah; Hari Rahman Hakim; Siti Lutfi Latifah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the innovation of agropreneurship-based education management in strengthening the economic development of Pesantren Persatuan Islam (PPI) 97 Cikajang. Employing a qualitative approach with a single case study design, data were collected through in-depth interviews, participant observations, document analysis, and Focus Group Discussions (FGDs). The findings reveal that the pesantren successfully formulated an innovative educational model that integrates religious learning, agribusiness skills, experiential learning, and productive entrepreneurial practices. The implementation of innovation occurred gradually and contextually, supported by visionary leadership, adequate infrastructure, competent human resources, and strong partnership networks. Nevertheless, several challenges were identified, including limited technical competencies, financial constraints, agricultural market fluctuations, and internal cultural resistance. The innovation has significantly contributed to increasing pesantren income, diversifying economic resources, optimizing productive assets, and enhancing students’ technical, managerial, and entrepreneurial competencies. This study offers a conceptual model of agropreneurship-based education management innovation that can serve as a reference for strengthening the economic independence of pesantren in Indonesia.